Product innovation toolbox : a field guide to consumer understanding and research - Beckley, Jacqueline H.; Paredes, Maria Dulce; Lopetcharat, Kannapon (Hoboken : John Wiley & Sons, 2012)
Product Innovation Toolbox: A Field Guide to Consumer Understanding and Research brings together key thought-leaders and seasoned consumer researchers from corporate R & D, academia and marketing research companies to share their experiences, cutting edge consumer research tools and practical tips for successful and sustainable product innovation. This is an essential resource for product developers, marketers and technologists who want to implement consumer-centric innovation and are responsible for designing product-testing strategies from upfront innovation to support new product development. The scope of the book by chapter shows the steps that transform a consumer researcher to a Consumer Explorer that guides the project team to successful innovation and new product introductions. Product Innovation Toolbox is designed to appeal to broad audiences from consumer researchers, product developers, marketers and executives. With an emphasis on consumer understanding and examples that range from cheese to lipstick and printers to energy beverages, Product Innovation Toolbox offers guidelines and best practices for strategizing, planning and executing studies with confidence and high efficiency yielding faster and better insights.
Product Innovation Toolbox: A Field Guide to Consumer Understanding and Research; Contents; Contributors; Acknowledgments; Introduction: From Pixel to Picture; Scoping the innovation landscape; How this book is organized; Part I; Part II; Part III; References; PART I STARTING THE JOURNEY AS A CONSUMER EXPLORER; 1 Setting the Direction: First, Know Where You Are; 1.1 Roles in the corporation -- the dance of the knowledge worker; 1.2 Insights leader -- learning on the job versus learning in school; 1.3 Being the authentic you; 1.4 What should you read?; 1.5 What else do you need to do to prepare to be an insight leader?1.6 Dealing with management and your clients; 1.7 Guidelines to success; 1.8 Reporting results; 1.9 Do not "winstonize"; 1.10 Making it public -- helpful hints to grow from student to professional; 1.11 The two types of professionals in the world of evaluating products (and studying consumers); 1.12 Knowing your limits and inviting others in; 1.13 The bottom line -- what's it all about?; References; 2 The Consumer Explorer: The Key to Delivering the Innovation Strategy; 2.1 You as a brand; 2.2 The roles of the Consumer Explorer2.3 Taking the lead; 2.4 Practical advice from seasoned Consumer Explorers; References; 3 Invention and Innovation; 3.1 Invention and innovation; 3.2 The steam engine: Watt and Boulton; 3.3 Nike: Bowerman and Knight; 3.4 The US Navy: Scott and Sims; 3.5 Consumer-perceived benefits: Coffee, beer and cigarettes; 3.6 Extensibility: Is there a limit to it?; 3.7 Innovation in scaling intensities and emotions; 3.8 Scaling intensities; 3.9 Scaling emotions (hedonics); 3.10 Final remarks; References; 4 Designing the Research Model; 4.1 Factors influencing product innovation4.2 Setting up a successful product innovation program; 4.3 Current approach to new product development; 4.4 Iterative qualitative-quantitative research model; References; 5 What You Must Look For: Finding High Potential Insights; 5.1 What is an insight?; 5.2 What is an "ownable" insight?; 5.3 How to develop high potential insights; 5.4 Behavior: The basis for all insights; 5.5 Attitudes and needs: The explanation for behavior; 5.6 Demographics and lifestyles: The personal connection; 5.7 Making insights ownable; 5.8 Summary; References; PART II RESEARCH TOOLS OF THE CONSUMER EXPLORER6 Tools for Up-Front Research on Consumer Triggers and Barriers; 6.1 Understanding Consumer Languages; 6.1.1 Consumers do not understand these technical words, so what should we say about our new products?; 6.1.2 How to select a method; 6.1.3 Free elicitation and Zaltman metaphor elicitation technique; 6.1.4 Laddering interview; 6.1.5 Potential problems when applying laddering interview in practice; 6.1.6 Kelly's repertory grid and flash profiling; 6.1.7 Summary and future; References; 6.2 Insights Through Immersion; 6.2.1 The power of immersive experience.
Print version record.
Keywords: New products; Consumer behavior; Marketing research; Consumer behavior; Marketing research; New products; BUSINESS & ECONOMICS -- Marketing -- Research; Consumer behavior; Marketing research; New products; Electronic books